Managing Anxiety: A Case Study of an International Teaching Assistant’s Interaction with American Students - Zhou, Ji (Journal of International Students, 2014)
This case study utilizes structuration theory to explore the complexities in the academic interaction between a Chinese international teaching assistant (ITA) and her American students. Through four semi-structured participant interviews, eight classroom observations, and student feedback, major themes and variations were identified regarding the feelings, concerns, and strategies of the ITA’s interaction with American students from the ITA perspective. The assumption is that despite the possible obstacles in cross-linguistic and cross-cultural academic interaction, ITAs have the drive and potential to successfully navigate through the challenging process. Implications for improving ITA training and practices are discussed.